Design Of Multiband Matched Band-Stop Filter Using T-Shape Resonator Network System. - Zakaria, Zahriladha; Hassan, Nornikman; Ismail, Mohd Khairy; Ahmad, Badrul Hisham; Nordin, Nurul Syahira; Zahari, Mohd Khairy; Abdul Malek, Mohd Fareq (Little Lion Scientific, 2018)
Wireless communication system is a system that transfer information among two or more points that are not connected by an electrical conductor while microwave filter is the elementary element in each radio frequency (RF) front-end telecommunication structure,moreover as band reject or band select components for transceivers and receivers.In designing a complicated wireless communication system or any other system that is working at microwave frequencies,noise is one of the big challenges.One of the techniques that can be used to avoid noise,or any other interference signal is by applying filtering techniques.For microwave communication front-end system,a band-stop filter can separate frequency band positioned inside a wide-ranging pass-band.Firstly,a single-band matched band-stop filter using T-shape resonator.Two different design had been done at 1.0 GHz and 1.5 GHz with S21 center frequency at – 16.063 dB and – 14.059 dB,respectively.Then,the combination of the multiband matched band-stop filter using T-shape resonator will be design at center frequencies of 1.0 GHz and 1.5 GHz with two S21 center frequency at – 16.281 dB and – 16.962 dB,respectively.The simulation process for this design is using Advanced Design System (ADS) simulation software and fabricated using FR-4 board.In real situation,this project will be able to isolate the signal of interest from interference signals at desired frequencies.